Short term respiratory health effects of ambient air pollution: results of the APHEA project in Paris. (April 1996) - Dab, W; Medina, S; Quénel, P; Le Moullec, Y; Le Tertre, A; Thelot, B; Monteil, C; Lameloise, P; Pirard, P; Momas, I; Ferry, R; Festy, B
Abstract : STUDY OBJECTIVE: To quantify the short term respiratory health effects of ambient air pollution in the Paris area. DESIGN: Time series analysis of daily pollution levels using Poisson regression. SETTING: Paris, 1987-92. MEASUREMENTS AND MAIN RESULTS: Air pollution was monitored by measurement of black smoke (BS) (15 monitoring stations), sulphur dioxide (SO2), nitrogen dioxide (NO2), particulate matter less than 13 microns in diameter (PM13), and ozone (O3) (4 stations). Daily mortality and general admissions to public hospitals due to respiratory causes were considered. The statistical analysis was based on a time series procedure using linear regression modelling followed by a Poisson regression. Meterological variables, epidemics of influenza A and B, and strikes of medical staff were included in the models. The mean daily concentration of PM13 and daily 1 hour maximum of SO2 significantly affected daily mortality from respiratory causes. An increase in the concentration of PM13 of 100 micrograms/m3 above its 5th centile value increased the risk of respiratory death by 17%. PM13 and BS were also associated with hospital admissions due to all respiratory diseases (4.1% increased risk when the BS level exceeded its 5th centile value by 100 micrograms/m3). SO2 levels consistently influenced hospital admissions for all respiratory diseases, chronic obstructive pulmonary disease, and asthma. Asthma was also correlated with NO2 levels. CONCLUSIONS: These results indicate that even though the relative risk is weak in areas with low levels of pollution, ambient air pollution, and especially particulate matter and SO2, nonetheless require attention because of the number of people exposed and the existence of high risk groups.